Preparation method and application of anode oxygen evolution catalyst
By doping chromium into the nickel-iron catalyst and adopting a layered hydroxide structure supported by foam nickel-supported nickel-iron catalyst, the stability problem of nickel-iron catalyst at high current density is solved, and higher electrochemical activity and long-term durability are achieved.
Patent Information
- Application Number
- CN202510028755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
AI Technical Summary
There are stability problems with nickel-iron catalysts under high current density, resulting in reduced catalyst activity and unstable structural structure.
The catalyst is prepared by hydrothermal reaction by using foam nickel-supported chromium-doped nickel-iron layered hydroxide. The doping of chromium can promote the reconstruction and structural stability of the nickel-iron catalyst.
The long-term durability of the catalyst under high current density is improved, the electrochemical active area is increased, the electrolyte penetration and ion diffusion are promoted, and the structural stability of the catalyst is maintained.
Smart Images

Figure CN119685873A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material synthesis and alkaline water electrolysis hydrogen production, and specifically relates to a preparation method and application of an anode oxygen evolution catalyst. Background Art
[0002] In the context of global energy structure transformation and the development of a green and low-carbon economy, research on green hydrogen production by water electrolysis is of great significance for promoting my country's green energy transformation, deep industrial decarbonization, and promoting sustainable economic and social development. Anion exchange membrane water electrolysis (AEMWE) technology and proton exchange membrane water electrolysis (PEMWE) technology have become key technologies for achieving efficient and large-scale green hydrogen production because they can be directly coupled with renewable energy. In particular, compared with technologies that are highly dependent on precious metals (such as Pt and IrO x )'s PEM water electrolysis technology, AEMWE technology can use the same low-cost non-precious metal catalysts as traditional alkaline (ALK) water electrolysis technology, making it more competitive in future industrial applications.
[0003] Nickel-iron-based catalysts have been identified as non-precious metal standard catalysts for alkaline oxygen evolution reaction (OER) due to their high catalytic activity in alkaline media. However, the catalyst undergoes reconstruction during the electrocatalytic oxygen evolution reaction to form nickel-iron oxyhydroxides. Although these in situ generated nickel-iron oxyhydroxides are the actual active sites, their poor conductivity leads to an increase in charge transfer resistance, which affects the activity and stability of the catalyst. Therefore, compared with powdered nickel-iron catalysts, in situ growth of nickel-iron-based catalysts on conductive substrates can effectively solve the above problems. In addition, at high anodic potentials, the iron in the nickel-iron catalyst undergoes a dynamic process of dissolution and redeposition. When operating at high current density, the dissolution of a large amount of iron may lead to a decrease in catalyst activity. The dissolution and redeposition of iron not only lead to iron segregation and phase separation, but also may destroy the structural stability of the catalyst.
[0004] To improve the stability of NiFe catalysts at high current density, researchers have tried a variety of strategies. For example, by incorporating stable oxygen-containing anions such as NO3 - ,CO3 2 ,SO4 2- The introduction of anions (such as ) into the catalyst lattice can effectively stabilize the iron species and inhibit their dissolution and segregation. These anions help maintain the structural stability of the catalyst under harsh OER conditions through strong chemical interactions with metallic iron sites. Another strategy is to achieve a uniform distribution of iron species on the catalyst surface through electrochemical reconstruction. Studies have shown that by controlling the electrode potential and electrolyte composition, uniform deposition of iron on the catalyst surface can be achieved, thereby reducing stability problems caused by iron segregation. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam.
[0008] In order to solve the above technical problems, the present invention provides the following technical solution: comprising the following steps: Untreated nickel foam with an area of 2 cm × 4 cm was placed in hydrochloric acid solution, deionized water and ethanol for ultrasonic treatment for a certain time; The treated nickel foam is obliquely inserted into a reactor filled with nickel salt, iron salt, chromium salt and a precipitant, and the reactor is placed in a blast oven for hydrothermal reaction. After the reaction is completed, it is naturally cooled to room temperature and washed with deionized water to obtain a chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam.
[0009] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the thickness of the nickel foam is 5 mm, the porosity is 65 ppi, and the concentration of the hydrochloric acid solution is 1-3 mol / L.
[0010] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the nickel foam is ultrasonically treated in hydrochloric acid solution, deionized water and anhydrous ethanol for 15 to 20 minutes respectively.
[0011] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the nickel salt, iron salt and chromium salt are nitrates, hydrochlorides and / or sulfates.
[0012] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the molar ratio of the nickel salt to the chromium salt is 30:(1-4).
[0013] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the molar ratio of the nickel salt to the iron salt+chromium salt is 1:1.
[0014] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the precipitant comprises urea, sodium sulfite, sodium phosphate and sodium thiosulfate, and the molar ratio of the nickel salt to the precipitant is 3:20.
[0015] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the concentration of the mixed salt solution of nickel, iron and chromium is 0.06-0.08 mol / L.
[0016] As a preferred embodiment of the method for preparing the anode oxygen evolution catalyst of the present invention, the hydrothermal reaction temperature is 110-130° C. and the reaction time is 4-6 hours.
[0017] As a preferred application of the anode oxygen evolution catalyst of the present invention, the prepared chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam is applied to anion exchange membrane water electrolysis.
[0018] Beneficial effects of the present invention: The present invention provides a preparation method and application of an anode oxygen evolution catalyst, and obtains a chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam, which has better long-term durability at high current density. In the OER process, the dissolution of chromium can promote the reconstruction of the nickel-iron catalyst, generate more active sites and pores, thereby increasing the electrochemical active area of the nickel-iron-based catalyst, and promoting the penetration of electrolytes and the diffusion of ions. In addition, the chromate anions partially present in the nickel-iron catalyst lattice can inhibit the dissolution and segregation of iron species, thereby maintaining the structural stability of the nickel-iron catalyst. The chromium-doped nickel-iron layered hydroxide anode catalyst supported by the method provided by the present invention is used as the anode of the anion exchange membrane water electrolysis device, combined with the anion exchange membrane and the cathode coated with commercial Raney nickel on carbon fiber paper to form a complete water electrolysis device for water electrolysis performance testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 The scanning electron microscope images and element distribution diagrams of the nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam prepared in Comparative Example 1 and the chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam prepared in Example 1.
[0020] Figure 2This is an activity comparison diagram of polarization curve tests of the chromium-doped nickel-iron layered hydroxide supported by nickel foam prepared in Example 1 and the nickel-iron layered hydroxide supported by nickel foam prepared in the prior art (Comparative Example 1) in 1M KOH solution.
[0021] Figure 3 The chromium-doped nickel-iron layered hydroxide supported by nickel foam prepared in Example 1 and the nickel-iron layered hydroxide supported by nickel foam prepared in Comparative Example 1 of the prior art were tested at a high current density (100 mA·cm -2 )’s stability comparison chart.
[0022] Figure 4 This is a comparison chart of the water electrolysis performance of AEMWE devices assembled with chromium-doped nickel-iron layered hydroxide supported by nickel foam prepared in Example 1 and undoped nickel-iron layered hydroxide supported by nickel foam prepared in Comparative Example 1 as anode oxygen evolution catalyst and commercial Raney nickel as cathode catalyst.
[0023] Figure 5 This is a comparison chart of the water electrolysis performance of AEMWE devices assembled with nickel-iron layered hydroxide supported by nickel foam with different chromium doping amounts prepared in Examples 1 to 4 and undoped nickel-iron layered hydroxide supported by nickel foam prepared in Comparative Example 1 as anode oxygen evolution catalyst and anion exchange membrane and commercial platinum-carbon as cathode catalyst, respectively. DETAILED DESCRIPTION
[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0025] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0026] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments. Example
[0027] This embodiment provides a method for preparing an anode oxygen evolution catalyst and its application, specifically: Preparation of chromium-doped nickel-iron layered hydroxide anodic oxygen evolution catalyst supported by nickel foam: An untreated nickel foam with an area of 2 cm×4 cm was ultrasonically treated in 3 mol / L hydrochloric acid solution, deionized water and anhydrous ethanol for 20 minutes respectively, and then immersed in anhydrous ethanol for later use.
[0028] Weigh 0.6 mmol of nickel nitrate, 0.6 mmol of iron nitrate, 0.06 mmol of chromium nitrate and 4 mmol of urea, dissolve them in 15 mL of deionized water, stir them ultrasonically, and transfer them to a 25 mL reactor after they are completely dissolved.
[0029] Subsequently, the pretreated nickel foam was inserted obliquely into the reactor, and the reactor was placed in a forced air oven, which was set to rise from room temperature to 120° C. within 10 minutes and then kept at 120° C. for 5 hours.
[0030] After the reaction is completed, the mixture is naturally cooled to room temperature, and the nickel foam is taken out from the reactor, rinsed with deionized water, and finally placed in a vacuum oven and dried at 60° C. for 12 hours.
[0031] Preparation of undoped nickel foam supported nickel-iron layered hydroxide anodic oxygen evolution catalyst: An untreated nickel foam with an area of 2 cm×4 cm was ultrasonically treated in 3 mol / L hydrochloric acid solution, deionized water and anhydrous ethanol for 20 minutes respectively, and then immersed in anhydrous ethanol for later use.
[0032] Weigh 0.6 mmol of nickel nitrate, 0.6 mmol of iron nitrate and 4 mmol of urea, dissolve them in 15 mL of deionized water, stir them ultrasonically, and transfer them to a 25 mL reactor after they are completely dissolved.
[0033] Subsequently, the pretreated nickel foam was inserted obliquely into the reactor, and the reactor was placed in a forced air oven, which was set to rise from room temperature to 120° C. within 10 minutes and then kept at 120° C. for 5 hours.
[0034] After the reaction is completed, the mixture is naturally cooled to room temperature, and the nickel foam is taken out from the reactor, rinsed with deionized water, and finally placed in a vacuum oven and dried at 60° C. for 12 hours.
[0035] Depend on Figure 1 It can be seen that the morphology of the chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by the nickel foam prepared by the method described in Example 1 is significantly different from the morphology of the undoped nickel foam supported nickel-iron layered hydroxide prepared in Comparative Example 1. The nickel foam supported nickel-iron layered hydroxide prepared by the prior art presents a microscopic morphology of a nanosheet array, while the morphology of the transition metal chromium-doped nickel-iron hydroxide is a nanoflower ball composed of nanosheets. In addition, it can be seen from the element distribution diagram that the chromium element is uniformly distributed in the nickel-iron hydroxide.
[0036] The test method for the activity and stability of the chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst prepared by the present invention on the nickel foam support in the three-electrode system is as follows: The prepared nickel foam supported chromium doped nickel iron layered hydroxide anodic oxygen evolution catalyst was cut into small pieces with an area of 0.5 cm × 1.5 cm and clamped on an electrode clamp as a working electrode. Its effective area in the electrolyte was 0.5 cm × 1 cm. Mercury / mercuric oxide electrode and graphite carbon rod were used as reference electrode and counter electrode respectively. In a standard three-electrode system, the catalyst prepared by the above method was subjected to polarization curve test in 1M KOH solution using an electrochemical workstation (CHI660e). The voltage range was set to 1~1.8V (vsRHE). The sample was activated by CV in this range, and then the scan rate was 5mV·s -1 The LSV polarization curve test was carried out; the stability test was carried out using a segmented it program test, with each segment current set to 0.05A and the time being 100000s. The experimental results are shown in Figure 2 and 3 .
[0037] Based on the polarization curve and stability test results, the nickel foam supported chromium doped nickel iron layered hydroxide anodic oxygen evolution catalyst prepared by the above method exhibits high OER activity and stability. Compared with the nickel foam supported nickel iron layered hydroxide prepared by the prior art, the nickel foam supported chromium doped nickel iron layered hydroxide anodic oxygen evolution catalyst prepared by the present invention requires lower voltage at the same current density, and has a higher OER activity and stability at a high current density (100 mA cm -2 ) After more than 100 hours of stability testing, its overpotential hardly increased, while the overpotential of the nickel-iron layered hydroxide supported by the nickel foam prepared by the prior art increased by 32 mV under the same conditions, which proves that the anodic oxygen evolution catalyst of the nickel-iron layered hydroxide supported by the chromium doped nickel foam prepared by the above method has better activity than that of the prior art (see Figure 2 ) and stability (see Figure 3 ).
[0038] AEMWE performance test method of the nickel foam-supported chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst prepared in the above-mentioned Example 1: Commercial Raney nickel was used as a cathode catalyst and prepared into a catalyst slurry (ink), which was sprayed on carbon fiber paper using an ultrasonic spraying device. The loading amount of the cathode catalyst was 2 mg / cm². The anion exchange membrane was a purchased 50 μm thick commercial anion exchange membrane (Sustainion-X37-50). The nickel foam-supported chromium-doped nickel-iron layered hydroxide material obtained in Example 1 and the undoped nickel foam-supported nickel-iron layered hydroxide obtained in the prior art (Comparative Example 1) were used as anode oxygen evolution catalysts of AEMWE, respectively. By circulating 1M KOH solution on the anode side, the polarization curve test of the AEMWE water electrolysis device was carried out. The performance of the AEM water electrolysis device is shown in FIG. Figure 3 .
[0039] Based on the AEMWE polarization curve test results, at 60°C, the nickel foam supported chromium doped nickel-iron layered hydroxide prepared in Example 1 is used as an AEMWE anode catalyst. When the current density reaches 2 A / cm², its potential is 1.97 V. This performance is better than the nickel foam supported nickel-iron layered hydroxide (2.1 V) prepared in the prior art (Comparative Example 1). Compared with the AEMWE water electrolysis device assembled with the nickel foam supported nickel-iron layered hydroxide prepared in the prior art (Comparative Example 1) as the anode, the AEMWE device assembled with the nickel foam supported chromium doped nickel-iron layered hydroxide prepared in Example 1 as the anode oxygen evolution catalyst has higher catalytic activity and lower cell pressure.
[0040] The amount of chromium salt added was changed (see Table 1), and the obtained nickel-iron layered hydroxide catalyst supported by nickel foam doped with different contents of chromium was used as the anode catalyst of AEMWE, commercial Pt / C was used as the cathode catalyst, and assembled with an anion exchange membrane into an AEMWE water electrolysis device for performance testing. The other conditions were the same as in Example 1.
[0041] Commercial Pt / C was used as a cathode catalyst to prepare a catalyst slurry (ink), and the cathode catalyst ink was sprayed on the carbon fiber paper using an ultrasonic spraying device, so that the cathode catalyst loading was 2 mg / cm². The anion exchange membrane was a purchased 50 μm thick commercial anion exchange membrane (Sustainion-X37-50).
[0042] According to the results obtained in Cases 1 to 4, the chromium-doped nickel-iron layered hydroxide material supported by nickel foam and the nickel-iron layered hydroxide supported by nickel foam prepared by the prior art (Comparative Example 1) were used as the anode oxygen evolution catalyst of AEMWE, and the polarization curve of the AEMWE water electrolysis device was tested by circulating 1M KOH solution on the anode side. The performance of AEM water electrolysis is shown in FIG. Figure 4 .
[0043] By comparing different experimental cases, compared with the nickel foam supported nickel-iron layered hydroxide anode catalyst prepared by the prior art, the nickel foam supported chromium doped nickel-iron layered hydroxide anode catalyst provided by the present invention shows better performance in an industrial anion exchange membrane water electrolyzer (AEMWE) device. The nickel foam supported chromium doped nickel-iron layered hydroxide prepared in Example 1 has the best performance as an AEMWE anode catalyst.
[0044] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an anode oxygen evolution catalyst, characterized in that: The following steps are involved: Untreated nickel foam with an area of 2 cm × 4 cm was placed in hydrochloric acid solution, deionized water and ethanol for ultrasonic treatment for a certain time; The treated nickel foam is obliquely inserted into a reactor filled with nickel salt, iron salt, chromium salt and a precipitant, and the reactor is placed in a blast oven for hydrothermal reaction. After the reaction is completed, it is naturally cooled to room temperature and washed with deionized water to obtain a chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam.
2. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The thickness of the nickel foam is 5 mm, the porosity is 65 ppi, and the concentration of the hydrochloric acid solution is 1-3 mol / L.
3. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The nickel foam is ultrasonically treated in hydrochloric acid solution, deionized water and anhydrous ethanol for 15 to 20 minutes respectively.
4. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The nickel salt, iron salt and chromium salt are nitrates, hydrochlorides and / or sulfates.
5. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The molar ratio of the nickel salt to the chromium salt is 30:(1-4).
6. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The molar ratio of the nickel salt to the iron salt+chromium salt is 1:
1.
7. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The precipitant includes urea, sodium sulfite, sodium phosphate and sodium thiosulfate, and the molar ratio of the nickel salt to the precipitant is 3:
20.
8. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The concentration of the nickel, iron and chromium mixed salt solution is 0.06-0.08 mol / L.
9. The method for preparing an anode oxygen evolution catalyst according to claim 1, wherein: The hydrothermal reaction temperature is 110-130° C. and the reaction time is 4-6 hours.
10. An application of an anode oxygen evolution catalyst, characterized in that: The invention comprises the preparation method and application of the anode oxygen evolution catalyst as claimed in any one of claims 1 to 9, and also comprises applying the prepared chromium-doped nickel-iron layered hydroxide anode oxygen evolution catalyst supported by nickel foam to anion exchange membrane water electrolysis.